How Flexed-Point Organizations are applied by Companies facing Crises: A comparative Study in East Asia (China and Japan) - Abedah, Maher Mohammed (NIU Journal of Management Sciences, 2026)
The paper will analyze how the Chinese and Japanese companies have been managing (organizational) resilience as depicted by the Chinese and Japanese media coverage of the current crises affecting the world. The study is based on the data of 80 surveyed organizations (the mixed-method research design); it also explores interviews with the executives of the companies, as a result of which contingently approaches towards religious resilience become known. Strategic agility is a field that the Chinese companies are excelling in, where success is crucial in pushing ahead in a marketplace, and the ability to digitalize. Japanese firms have a good operating balance and strong cultural solidity, which is indicated by joint mindfulness and strong closeness of the interrelations between the stakeholders. In every one of these alternative paths to it, however, the two systems end up at the same point of similar stateful resilience - an embodiment of the principle of equip-finality in organizational resilience. In this paper, it was concluded that Chinese firms have flexibility and a competitive edge, within which organizational learning takes place. It is also claimed that this is done by the bodies so as not to disrupt objectives.60 Writers even suggest that such institutions should also strive to consider methods of how collective mindfulness and dynamic capabilities might be incorporated in the backup resilience plans within the cultural, industrial and / or institutional systems in which they are incorporated. Keywords: Chinese firms, Japanese firms, organizational resilience, crisis management.